Platelet Activating Factor/Platelet Activating Factor Receptor Pathway as a Potential Therapeutic Target in Autoimmune Diseases - Edwards, Laura J.; Constantinescu, Cris S. (Inflammation & Allergy-Drug Targets (Discontinued), 2009)
Platelet activating factor (PAF) is a phospholipid mediator of inflammation that is released early in inflammation by a variety of cell types. PAF acts largely by binding to its receptor, PAF-R, a G-protein coupled receptor found on a variety of cells, including cells of the immune system. PAF has been implicated in the pathogenesis of asthma and allergic conditions, but its role in autoimmune conditions has been less extensively investigated. Here, we review the accumulating evidence for the role of PAF/PAF-R pathway in autoimmune diseases. We describe studies showing up-regulation of PAF-R in inflammatory bowel disease, rheumatoid arthritis and multiple sclerosis and review the evidence from the use of PAF-R antagonists. We describe results of experimental models of inflammatory diseases that point to a role for PAF/PAF-R pathway including those using PAF-R antagonists and those employing PAF-R knockout mice and knockout mice for cytosolic phospholipase2. Recent experiments from our laboratory show that PAF/PAF-R pathway may influence T cell responses and favour the Th17 phenotype (in which T cells produce tissue destructive proinflammatory cytokine IL-17). The PAF/PAF-R pathway is a promising target for pharmacological intervention in autoimmune diseases.
Keywords: platelet activating factor receptor